Response of parasitoids to invasive pest Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) on cassava crop in Bali, Indonesia - I WAYAN SUPARTHA; I KADEK WISMA YUDHA; PUTU ANGGA WIRADANA; I WAYAN SUSILA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Supartha IW, Yudha IKW, Wiradana PA, Susila IW. 2020. Response of parasitoids to invasive pest Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) on cassava crop in Bali, Indonesia. Biodiversitas 21: 4543-4549. Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) is an invasive pest that entered Indonesia in 2010 and attacks cassava plants, especially in Bali Province. This study aimed to identify species and establish the population distribution mapping, community structures (diversity, abundance, and dominance), and parasitization rate on cassava crops in Bali. This study conducted with a field observation method by taking infested shoots of cassava plants by P. manihoti purposively in the field. The cassava mealybug that was present in the leaves or shoots were kept in the laboratory until the parasitoid appeared. The results showed that four species of parasitoids were found to respond to invasive pest, namely Anagyrus lopezi (Encyrtidae), Acerophagus sp. (Encyrtidae), Blepyrus sp. (Encyrtidae) and Encarsia sp. (Aphelinidae). Structurally the parasitoid community had a low abundance (R1 = 0.50–0.87) and low diversity index value (H'= 0.27-0.28). While the parasitoid dominance index was in the moderate category with a value D = 0.33–0.59 in Bangli, Klungkung, Badung, Tabanan, and Buleleng Districts. But it had high dominance index values in Gianyar, Denpasar, Jembrana, and Karangasem Districts with a value D = 0.62-0.72. The three species of parasitoid spread evenly in all districts and cities in Bali according to the host distribution map, namely P. manihoti on cassava crop. The four parasitoids showed varying parasitic levels in the field with the highest parasitization rate was A. lopezi followed by Acerophagus sp., Blepyrus sp., and Encarsia sp.